Planejamento da rede de distribuição de medicamentos considerando custos logísticos e de ICMS - Ramos, Cindy (2019)
Medicines distribution planning in Brazil involves decisions of logistics network configuration, related to the location of distribution centers (DCs) and product flow among facilities. Medicines distribution planning in Brazil faces some challenges, due to medicines have many different characteristics, concerning to physical attributes (weight and volume), demand patterns and high value-added of the products. Other relevant issue is the Tax on Circulation of Goods and Services (ICMS). This tax depends on the value-added of the products and can significantly affect the distribution network planning. The ICMS is a non-cumulative tax, with rates that vary among states and results in a differentiated tax structure along the supply chain. In this work, we proposed an optimization model to support decisions of DCs location and the customer demand allocation to these DCs. We considered transportation costs, products of different values, interstate and intrastate rates and the matching credit (a tax benefit) offered by some Brazilian States. We used real data from a previous study and analyzed the solutions model to understand the relationships between logistics costs and taxation costs for each region/state. The allocation of lower value-added products depends more on logistics costs, while the allocation of higher value-added products is determine by the tax costs. However, a detailed assessment of the relationship between costs demystifies the advantage of tax benefits, especially for products where unit transport costs are higher than ICMS unit costs.